Curriculum development in the higher education literature: A synthesis focusing on construction management programmes. Issue 4 (August 2022) - Posillico, John J; Edwards, David J; Roberts, Chris; Shelbourn, Mark
This research first contextualises curriculum development in higher education institutions (HEIs) before focusing specifically on construction management programmes in order to engender wider polemic discourse and new insights into current provisions. The overarching epistemology adopts both interpretivist and pragmatist philosophical stances, couched within inductive reasoning, to critically analyse extant literature as a secondary data source, with each publication representing a unit of analysis. Thematic groupings of research activity are then clustered and interconnections between researchers and research themes are identified using bibliometrics. The findings illustrate that while curriculum development in HEIs has received increasing scrutiny and attention, there is a notable lack of connectivity among the studies conducted. This lack of a cohesive body of knowledge is exacerbated by the prevailing academic notion of 'individualism and self' vis-a-vis the 'collective team'. This leads to an emergent working hypothesis, namely, that bespoke curriculum development occurs within an 'every person for themselves' mentality. Cumulatively, these issues reported upon serve to illustrate a fundamental absence of a clear agenda for curriculum development in construction management programmes. In turn, this finding underscores the urgent need for a more prominent collaborative and global community of practice to optimise future educational provisions.